Effects of O-(4-ethoxyl-butyl)-berbamine on isolated frog hearts - Zheng Guang-Hua; Chen Zhong-Lun; Jiang Jia-Hua (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of O-(4-ethoxyl-butyl)-berbamine (EBB) on isolated frog heart. METHODS: The isolated frog hearts were prepared with Straub's method; heart contractions were recorded using LMS-2A recorder by tonotransducer. RESULTS: EBB 1-100 mumol.L-1 caused concentration-dependent increase in systolic and diastolic activities, but did not alter the heart rate. EBB 250-500 mumol.L-1 slowed the heart beats and caused ventricular asystole. Cimetidine 10 mumol.L-1 or prazosin 100 mumol.L-1 did not inhibit the positive inotropic action of EBB. Whereas verapamil 0.01 mumol.L-1 antagonized the positive inotropic action of EBB. EBB enhanced positive inotropic action of CaCl2. The action of EBB was slower but longer than caffeine or isoproterenol. At room temperature (21.0 +/- 0.5) degree C, however, the onset of oubain was slower, but the duration of its peak action was longer, than EBB. CONCLUSION: The positive inotropic action of EBB was, at least partially, via promoting the inward current of [Ca2+]o, rather than increasing the intracellular Ca2+ release.